Impact of Fresh Table Grape Intake on Circulating microRNAs Levels in Healthy Subjects: A Significant Modulation of Gastrointestinal Cancer‐Related Pathways. Issue 21 (21st September 2021) - Tutino, Valeria; De Nunzio, Valentina; Milella, Rosa Anna; Gasparro, Marica; Cisternino, Anna Maria; Gigante, Isabella; Lanzilotta, Elsa; Iacovazzi, Palma Aurelia; Lippolis, Antonio; Lippolis, Tamara; Caruso, Maria Gabriella; Notarnicola, Maria
Abstract : Scope: The study aims to investigate the effects of fresh table grape consumption in healthy subjects on circulating levels of the most common human microRNAs (miRNAs). The regulatory network governed by these modulated miRNAs is also investigated. Methods and Results: Autumn Royal table grape, used in this study, is chosen for its high polyphenolic content and antioxidant properties. The study is a randomized controlled trial, in which 40 consecutive subjects are recruited on a voluntary basis and randomly assigned to two groups of the study, the control group, receiving only dietary recommendations and a grape group receiving a daily dose of 5 g of fresh table grape per kg of body weight for 21 days. All analyses are performed at baseline and after 21 days of dietary treatment. Circulating miRNAs levels are detected by Real‐Time quantitative PCR (RT‐qPCR) followed by bioinformatic functional analysis. The study identifies 20 circulating miRNAs differentially expressed in healthy subjects after grape intake, and in particular, 18 of 20 are down‐regulated and 2 are up‐regulated. Conclusion: The dietary intake of table grape affects circulating miRNAs levels in healthy subjects, particularly the miRNAs related to pathways involved in counteracting cancer development, including gastrointestinal cancers. Abstract : This study demonstrates that a grape‐rich diet shows a great impact on human health through modulation of small RNA molecules, namely miRNAs found in serum. In this study, 20 circulating miRNAs differentially expresses after grape intake are identified, and notably, most of them are molecules down‐expressed by grape treatment and linked to pathways involved in cancer development, including colorectal and pancreatic cancer.